Performance of The Selected Main Tree of Liberoid Coffe in The Peatland of Meranti Island, Riau - Budi Martono (Center for Journal Management and Publication, 2017)
In order to develop (renewal and extension) the Liberoid coffee in peatland, it is necessary to do the program of increasing production and quality of Liberoid coffee. It requires the superior planting materials of superior in specific location. This study has the objective to find out the performance of the selected main trees of Liberoid coffee. The study was conducted from January to September 2015 in the area of peatland in the Kedaburapat village, Rangsang Pesisir District, Kepulauan Meranti Regency, Riau. The method used was the direct observation of main trees of selected Liberoid coffee. The observed character is quantitative and qualitative character. The results showed the diversity of quantitative characters within a range between 7.39 to 40.11%. The average number of pieces / bunch is third with a production of 30.63 kg / tree / year, 288.25 cm plant height, stem diameter 36.88 cm, the number of primary branches of 5.88; the number of secondary branches 12.63, crown width 185.88 cm western, eastern 201.13 cm, 209.25 cm southern and northern 216.75 cm. The diversity of qualitative character is seen in the character of shoot color, old fruit color, fruit shape, fruit discuss, and the upper surface of the leaf.